2020
DOI: 10.3390/cancers12113437
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Cancer Properties of the HIV Protease Inhibitor Nelfinavir

Abstract: Traditional cancer treatments may lose efficacy following the emergence of novel mutations or the development of chemoradiotherapy resistance. Late diagnosis, high-cost of treatment, and the requirement of highly efficient infrastructure to dispense cancer therapies hinder the availability of adequate treatment in low-income and resource-limited settings. Repositioning approved drugs as cancer therapeutics may reduce the cost and timeline for novel drug development and expedite the availability of newer, effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 146 publications
(370 reference statements)
0
29
0
Order By: Relevance
“…The anti-tumor effects of metformin combined with nelfinavir on cervical cancer cell xenograft nude mice were investigated by Xia et al [ 84 ]. In addition, the anti-cancer properties of nelfinavir, an HIV protease inhibitor, have been explored [ 99 ]. The effects of nelfinavir on NSCLC cells and tumor xenografts in nude mice were investigated [ 100 ]; moreover, it was found that the effect of docetaxel on inhibiting the growth of NCI-H460 and -H520 cells could be enhanced by nelfinavir [ 100 ].…”
Section: Combination Of Metformin With Therapeutic Agents Induced Anti-cervical Cancer Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-tumor effects of metformin combined with nelfinavir on cervical cancer cell xenograft nude mice were investigated by Xia et al [ 84 ]. In addition, the anti-cancer properties of nelfinavir, an HIV protease inhibitor, have been explored [ 99 ]. The effects of nelfinavir on NSCLC cells and tumor xenografts in nude mice were investigated [ 100 ]; moreover, it was found that the effect of docetaxel on inhibiting the growth of NCI-H460 and -H520 cells could be enhanced by nelfinavir [ 100 ].…”
Section: Combination Of Metformin With Therapeutic Agents Induced Anti-cervical Cancer Effectsmentioning
confidence: 99%
“…Nelfinavir exerts anticancer effects, including cell-cycle arrest, cell death, endoplasmic reticulum stress, unfolded protein response, autophagy, inhibition of proteasomes, and downregulation of Akt signaling, alters the tumor microenvironment, and can be used in multidrug efflux pumps [ 99 ]. The effects of metformin in combination with nelfinavir include synergistic effects against growth, inhibition, migration and invasion, upregulating the expressions of ROS, p53 and p2, and downregulating the expression of PI3K(p110α) in cervical cancer cell xenograft nude mice [ 84 ].…”
Section: Combination Of Metformin With Therapeutic Agents Induced Anti-cervical Cancer Effectsmentioning
confidence: 99%
“…Depending on the type of cancer and treatment regimen, NFV has also been shown to modulate cell cycle, cell death, signal transduction pathways, autophagy, the proteasome pathway, the tumor microenvironment, oxidative stress, and multidrug efflux pumps [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated the capability of many PRIs to inhibit not only the primary target, but also other ones involved in the regulation of glucose and lipids homeostasis, as well as cell proliferation and survival [ 30 , 33 , 34 , 35 , 36 ]. Indeed, from a biomolecular point of view, this evidence is reported in the literature and describes the capability of HIV-1 PRIs to inhibit the Akt, EGFR, and IGF1-R pathways involved in the regulation of metabolic processes, and also investigated in anticancer therapy [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%